Assessment of Some Immune Parameters in Occupationally Exposed Nuclear Power Plant Workers - Ilona Mihaylova Gyuleva; Kalina Ivanova Penkova; Ivanka Tankova Rupova; Delyana Yonkova Panova; Jana Nikolaeva Djounova (SAGE Publishing, 2015)
A 10-year survey of immune status of nuclear power plant (NPP) workers was assessed by cellular and humoral immune parameters. The cumulative doses of NPP workers were in the range of 0.06 to 766.36 mSv. The results did not show significant deviations in the studied parameters of cellular and humoral immunity, but a tendency of elevated values in CD3+4+ helper inducers cells, especially its CD4+62L+ subpopulation, regulatory CD4+25+ cells, CD8+28+ cytotoxic subpopulation, and immunoglobulin M, was established. The observed trend of the above-mentioned parameters could be interpreted by assumption that while the adaptation processes are dominated with low prevalence of T-helper (Th) 1 immune response to cumulative doses less than 100 mSv, a switch to Th-2 response occurred at doses above 100 mSv. The impact of a number of other confounding factors on the immune system does not allow definitive conclusions about the direct radiation-induced changes in immune parameters.